DESCRIPTIVE STUDY OF RADIATION DOSE IN CBCT FOR DENTAL APPLICATION - Sari, Amillia Kartika; Rahmawati, Lusiana Fitri; Pramono, Pramono; Putra, Ayub Manggala; ‘Aisy Farhah, Ghinaa Rihadatul; Palupi, Endah Sekar (FKG ULM, 2026)
Background: Cone Beam Computed Tomography (CBCT) provides superior 3D imaging for dental diagnosis but involves higher radiation exposure than conventional radiography. Therefore, dose optimization based on the ALARA principle and the establishment of Diagnostic Reference Levels (DRLs) are essential for patient safety and radiation protection. Purpose: This study evaluated CBCT exposure parameters and radiation dose variation by FOV to support dose optimization and DRL development. Methods: This retrospective descriptive study analyzed CBCT records of adult patients (September 2023–2024). Variables included tube voltage, tube current, exposure time, voxel size, DAP, Effective Dose, and FOV. Data were analyzed using descriptive statistics and FOV-based comparisons with SPSS version 30. Results: A total of 50 patients were included (56% female and 44% male) had average exposure parameters of 89.80 kV, 2.87 mA, 15 seconds, and 0.148 mm voxel size. The 8x5 cm FOV (4 patients) produced a DAP of 721.50 µGy cm² and an Effective Dose of 70 µSv. The 8x9 cm FOV (46 patients) produced a DAP of 1151.48 µGy cm² and an Effective Dose of 72 µSv. The typical dose value (Q2 DAP) was 1179 µGy cm². Conclusion: Radiation doses in dental CBCT examinations vary depending on the FOV size, with larger FOVs resulting in higher radiation exposure. Selecting the appropriate FOV based on clinical indications, along with dose monitoring and establishing Diagnostic Reference Levels (DRLs), is crucial for optimizing patient safety and radiation protection in dental radiology. Keywords: Cone Beam Computed Tomography, DRL, Patient Safety, Radiation Protection, TDV